Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1080/15374410903532700
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Reported Homework Problems in the MTA Study: Evidence for Sustained Improvement with Behavioral Treatment

Abstract: Parent-report of child homework problems was examined as a treatment outcome variable in the MTA - Multimodal Treatment Study of Children with Attention-Deficit/Hyperactivity Disorder (ADHD). Five hundred seventy-nine children ages 7.0–9.9 were randomly assigned to either medication management, behavioral treatment, combination treatment, or routine community care. Results showed that only participants who received behavioral treatment (behavioral and combined treatment) demonstrated sustained improvements in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 52 publications
4
44
0
2
Order By: Relevance
“…This findings are consistent with the experimental results in which self-monitoring programs for attention are described as effective treatment for improving attention in ADHD students (Langberg et al, 2010;Reid, Trout, & Schartz, 2005;DuPaul, Eckert, & Vilardo, 2012;Albano & Kendall, 2002). Although self-monitoring program, as a form of cognitive-behavioral therapy, seems to be reasonable for improving attention's behaviors, the results of the studies in this field were not as clear and distinctive as behavioral therapy techniques.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This findings are consistent with the experimental results in which self-monitoring programs for attention are described as effective treatment for improving attention in ADHD students (Langberg et al, 2010;Reid, Trout, & Schartz, 2005;DuPaul, Eckert, & Vilardo, 2012;Albano & Kendall, 2002). Although self-monitoring program, as a form of cognitive-behavioral therapy, seems to be reasonable for improving attention's behaviors, the results of the studies in this field were not as clear and distinctive as behavioral therapy techniques.…”
Section: Discussionsupporting
confidence: 79%
“…The disorder was recognized as the most common neurobehavioral disorder during childhood (Biederman & Faraone, 2005;Kendall & Comer, 2010;Barkley, DuPaul, & McMurray, 1990). Due to its relatively high importance and prevalence (3-5 percent), medication and psychological treatments were administered for the disorder and extensive studies were carried out on the effectiveness of these psychotherapeutic techniques (Langberg et al, 2010;Nelson, Benner, & Mooney, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We identified six studies that reported the results of treatments that combine aspects of BPT, BCM, and/or BPI. Given prior evidence supporting BPT and BCM, it is not surprising that these studies reported numerous benefits for the combined treatment relative to a no treatment condition or to an active psychosocial support intervention (Abikoff, Gallagher, Wells, Murray, Huang, & Feinham, 2013;Kern et al, 2007;Langberg et al, 2010;Pfiffner et al, 2007;Power et al, 2012; Webster-Stratton, Reid, & Beauchaine, 2011). Possible mediators and moderators were only examined in the study by Langberg and colleagues (2010).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…When stimulants are used to treat children with ADHD, combining behavior therapy with stimulant medication tends to be more readily accepted by parents (MTA Cooperative Group, 2004) and enhances the likelihood for reduction of medication dosage (Vitiello et al, 2001) compared to use of stimulants alone. There is extensive research supporting behavior therapy as an effective intervention for individuals with ADHD (Fabiano et al, 2009;Pelham & Fabiano, 2008), even in the absence of stimulant medication (Flood, Wilder, Flood, & Masuda, 2002;Langberg et al, 2010). Several behavioral interventions have evidence-based support for improving outcomes for students with ADHD in the classroom (Azrin, Vinas, & Ehle, 2007;Brasch, Williams, & McLaughlin, 2008;Tobin, Schneider, Reck, & Landau, 2008).…”
mentioning
confidence: 95%